Bahasa Inggris Bahasa Indonesia: Bahasa Indonesia - Mulyana, Rendi; Prabawati, Mega Nur; Madawistama, Sri Tirto (De Fermat : Jurnal Pendidikan Matematika, 2026)
This study aims to examine the feasibility of a learning media developed using iSpring Suite 11 on integer material to enhance junior high school students’ mathematical literacy skills. The research employed a Research and Development (R&D) method using the ADDIE model. Data collection techniques included preliminary tests and interviews. The instruments used were mathematical literacy test items, interview guideline sheets, feasibility assessment sheets, and student response questionnaires. The data sources consisted of two subject matter experts, two instructional design experts, and two learning media experts who evaluated the technical quality of the media. Additionally, seventh-grade students of SMP Muhammadiyah Tasikmalaya were involved to assess the practicality of the developed media. The result of this study is an Android-based learning media application named MathReality. The feasibility of the media was evaluated based on content, design, and visual aspects. This learning media was declared highly feasible based on the questionnaire results, with assessment percentages of 84% from the subject matter expert, 93% from the instructional design expert, and 98% from the learning media expert. Furthermore, students showed very positive responses toward the practicality of the media, as indicated by a questionnaire result of 92%.